Genotype–phenotype correlation study in 364 osteogenesis imperfecta Italian patients - Maioli, Margherita; Gnoli, Maria; Boarini, Manila; Tremosini, Morena; Zambrano, Anna; Pedrini, Elena; Mordenti, Marina; Corsini, Serena; D’Eufemia, Patrizia; Versacci, Paolo; Celli, Mauro; Sangiorgi, Luca (European journal of human genetics : EJHG, 2019)
Osteogenesis imperfecta (OI) is a rare genetic disorder of the connective tissue and 90% of cases are due to dominant mutations in COL1A1 and COL1A2 genes. To increase OI disease knowledge and contribute to patient follow-up management, a homogeneous Italian cohort of 364 subjects affected by OI types I-IV was evaluated. The study population was composed of 262 OI type I, 24 type II, 39 type III, and 39 type IV patients. Three hundred and nine subjects had a type I collagen affecting function mutations (230 in α1(I) and 79 in α2(I)); no disease-causing changes were noticed in 55 patients. Compared with previous genotype-phenotype OI correlation studies, additional observations arose: a new effect for α1- and α2-serine substitutions has been pointed out and heart defects, never considered before, resulted associated to quantitative mutations (P = 0.043). Moreover, some different findings emerged if compared with previous literature; especially, focusing the attention on the lethal form, no association with specific collagen regions was found and most of variants localized in the previously reported "lethal clusters" were causative of OI types I-IV. Some discrepancies have been highlighted also considering the "50-55 nucleotides rule," as well as the relationship between specific collagen I mutated region and the presence of dentinogenesis imperfecta and/or blue sclera. Despite difficulties still present in defining clear rules to predict the clinical outcome in OI patients, this study provides new pieces for completing the puzzle, also thanks to the inclusion of clinical signs never considered before and to the large number of OI Italian patients.